Implementation of Automated Lines for Sorting and Recycling Household Waste as an Important Goal of Environmental Protection - KRECHETOV, Ivan V.; SKVORTSOV, Arkadiy A.; POSELSKY, Ivan A.; PALTSEV, Sergey A.; LAVRIKOV, Pavel S.; KOROTKOVS, Vladislavs (Journal of Environmental Management and Tourism; Vol 9 No 8 (2018): JEMT Volume IX Issue 8(32) Winter 2018DO - 10.14505//jemt.v9.8(32).21, 2019)
The principles of selection and creation of rational methods of disposal and recycling of wastes are based on the fact that the problem of waste is an interconnected environmental-economic and technological problem, and the waste itself should be considered as technogenic raw materials of complex organo-mineral composition. Therefore, the main purpose of the work is to define methods for recycling waste and their environmental aspects. To achieve this goal, the methods of analysis, spectroscopy were used. It is determined that the final treatment of waste, to date, means either their disposal in a landfill or incineration, which adversely affects the environment. Methods for identifying the material of the object, as well as algorithms for the selection and recognition of objects by processing data from the computer vision system are considered. High accuracy is shown in 94.12% identification of plastic polymers.